Effects of long-term nitrogen and phosphorus addition on plant defence compounds in a freshwater wetland. (November 2018) - Shan, Liping; Song, Changchun; Zhang, Xinhou; Ren, Jiusheng
Graphical abstract: Highlights: 12-yr N addition and 10-yr P addition experiments were conducted. Nutrient addition decreased the production of defence compounds in plant leaves. Leaves are more sensitive to relative resource availability compared with stems. Nutrient enrichment altered plant carbon allocation to secondary metabolites. Nutrient enrichment would influence nutrient cycling in freshwater wetlands. Abstract: Prominent theories of plant defence have predicted that alleviating nutrient limitation will result in decreased production of defence compounds. Yet effects of nutrient addition on plant defence compounds have been found to vary, and research on plant resource allocation in different organs in response to long-term nutrient addition is limited. In this study, we aimed to elucidate effects of 12-yr nitrogen (N) addition and 10-yr phosphorus (P) addition on plant defence compounds (total polyphenols, condensed tannins, cellulose and lignin) in both leaves and stems of dominant specie Glyceria spiculosa in a freshwater wetland in the Sanjiang Plain, Northeast China. Both N addition and P addition reduced the production of defence compounds in plant leaves, but increased the production of lignin in the stems. Notably, the concentrations of plant secondary metabolites closely correlated with the plant C:N:P stoichiometric ratios. The results suggest that long-term nutrient addition can alter plant carbon allocation to C-based defence compounds, and thus potentially exert influences on nutrient cycling and ecological processes in freshwater wetlands.